The hunting - Hawksmoor, Sam (London: Hodder Children's, 2012)
Genie and Rian thought they had beaten The Fortress and stopped the dreadful experiments. But now someone even more ruthless has taken over, and wants to investigate why the experiments didn't kill Genie Magee. She is Fortress property, he claims - along with the other survivors. Now there's $10,000 reward on their heads, armed roadblocks on the highway, and the dreaded threat of 'Mosquito' that can shut down their brainwaves by using their genetic information against them. There's only one possible escape from the bounty hunters with shotguns, and that's down the wild unforgiving river to a bleak future forever on the run. Or they must turn and face The Fortress, find out its secrets, and use them against it. Seize their lives back, and fight for their very right to exist!
Keywords: Young adult fiction